Free trade and protection with reference to Ireland - Coffey, George (Statistical and Social Inquiry Society of Ireland, 1886)
Some recent conversations on Free Trade and Protection with reference to Ireland, have suggested to me to bring before our Society the following short consideration of the subject. Within the next few years the question may become of more than academic interest to this country; and it is, I need not say, of importance that the ground of discussion should be in some measure cleared before entered on for action. In the present paper I have not attempted the collection or examination of statistics. The effect of English trade monopolies on Irish industries have, it is true, during the past few months received some attention in the press. But the impossibility of obtaining trustworthy information, and the danger of being led into basing conclusions on a few particular instances ?also, the difficulty of separating Irish returns from those of the United Kingdom, have inclined me to write rather with a view of suggesting lines of discussion than in any hope of final assertion.
Read Tuesday, 24th November, 1885
Keywords: Free trade; Open market; 314.15